A Bibliometric Study of Communicative Language Teaching in Indonesian High School and Vocational School - Arbain, Arbain; Rachman , Dzul; Anshori , Sakut; Nur, Dedi Rahman; Meiramova , Saltanat A.; Aswad , Muhammad (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2025)
The global shift toward communication-driven education has positioned Communicative Language Instruction (CLI) as a vital approach in teaching English, particularly in Indonesian secondary and vocational schools. Despite its increasing application, a systematic understanding of CLI's scholarly development remains limited. This study aims to fill that gap through a comprehensive bibliometric analysis of CLI research published between 2014 and 2024. Using structured searches across Google Scholar, Scopus, and Dimensions, an initial dataset of 223 articles was collected. After applying inclusion and exclusion criteria focusing on peer-reviewed studies in English as a Foreign Language (EFL) contexts, a total of 97 articles were selected for analysis. Bibliometric tools including VOSviewer and Publish or Perish (PoP) were employed to examine metadata such as publication trends, authorship patterns, keyword frequencies, and country distributions. The results show a substantial rise in CLI-related publications, from 7 in 2014 to a peak of 29 in both 2021 and 2022. Indonesia produced the highest number of studies (n = 11), followed by Iran (n = 10). Keyword co-occurrence revealed dominant themes such as